Pluralistic Da'wah Model in Maintaining Religious Tolerance in Bekasi - Deden Sumpena; Adon Nasurullah Jamaludin (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2020)
This article aims to explore perceptions of religious pluralism, identify the models of da'wah being carried out, and describe the community's efforts in building harmony between muslims and christians in Kampung Sawah Bekasi. This study uses a qualitative descriptive method. From the study results, it can be explained that the community interprets pluralism as an awareness of mutual respect. There are three da'wah models, namely, preaching that is wise, transformative, and inclusive preaching. Meanwhile, the community's efforts to maintain harmony include avoiding conflict, dialogue, cooperation, and holding the Ngariung Bareng Forum. The practical implications of this research impact efforts to build harmony and harmony between religious communities in Bekasi. Besides, research is expected to become a model for the development of da'wah in a pluralistic society.Artikel ini bertujuan menggali persepsi pluralisme agama, mengidentifikasi model dakwah yang dilakukan dan mendeskripsikan upaya masyarakat dalam membangun kerukunan umat Islam dan umat Kristen di Kampung Sawah Bekasi. Penelitian ini menggunakan metode deskriptif kualitatif. Dari hasil penelitian dapat dijelaskan bahwa masyarakat memaknai pluralisme sebagai kesadaran saling menghargai. Terdapat tiga model dakwah pluralistik yaitu; dakwah yang arif, dakwah transformatif dan dakwah inklusif. Sedangkan upaya masyarakat dalam menjaga kerukunan, yaitu dengan menghindari konflik; berdialog; gotong royong; dan menyelenggarakan Forum Ngariung Bareng. Implikasi praktis penelitian berdampak pada upaya membangun keharmonisan dan kerukunan antar umat beragama di Bekasi. Selain itu, penelitian diharapkan dapat menjadi model pengembangan dakwah pada masyarakat pluralistik.